2012
DOI: 10.1176/appi.ajp.2011.11030433
|View full text |Cite
|
Sign up to set email alerts
|

A Quality-Based Review of Randomized Controlled Trials of Cognitive-Behavioral Therapy for Depression: An Assessment and Metaregression

Abstract: On average, randomized controlled trials of CBT and of psychodynamic therapy did not differ significantly in quality. In CBT trials, low quality appeared to reduce the reliability and validity of trial results. These findings highlight the importance of discerning quality in individual psychotherapy trials and also point toward specific methodological standards for the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 34 publications
4
49
0
1
Order By: Relevance
“…This difference has been significant. That lower study quality seems to be related with larger effect sizes has also been confirmed by a more recent review [29]. Moreover, Cuijpers and collaborators [30] f o u n d t h a t i n d e p e n d e n c e o f t h e k i n d o f instrument used to measure improvement following a psychotherapy the effect sizes of studies examining the effect of psychotherapy for depression differ significantly so as to clinician-ratings are associated with a significantly greater effect size than are self-report measures.…”
Section: Effectiveness and Efficacy Of Cognitive Behavioral Therapy Isupporting
confidence: 55%
“…This difference has been significant. That lower study quality seems to be related with larger effect sizes has also been confirmed by a more recent review [29]. Moreover, Cuijpers and collaborators [30] f o u n d t h a t i n d e p e n d e n c e o f t h e k i n d o f instrument used to measure improvement following a psychotherapy the effect sizes of studies examining the effect of psychotherapy for depression differ significantly so as to clinician-ratings are associated with a significantly greater effect size than are self-report measures.…”
Section: Effectiveness and Efficacy Of Cognitive Behavioral Therapy Isupporting
confidence: 55%
“…In the 1970s, a group of cognitive therapists in Philadelphia led by Aaron T Beck listened cautiously to what their clients were saying and turned to learning theory and the cognitive revolution to formulate a new theoretical account and therapeutic approach to depression [23] . CBT, from its inception growing out of basic and applied research [37] , remains closely tied to ongoing research [38] , and is used to deal with IBS. It was designed to educate participants about physical, cognitive, and behavioral factors which contribute to IBS; thus teaching them methods of enhancing self-control over stress, anxiety, and IBS symptoms; to correct dysfunctional thoughts and to prevent symptom relapse [39] .…”
Section: Cbt and Application To Ibsmentioning
confidence: 99%
“…No substantial differences in efficacy between the different psychotherapeutic approaches have been found (Cuijpers et al 2014;Driessen et al 2015;Keefe et al 2014). Furthermore, the quality of studies for PDT does not differ from that of other approaches such as CBT (Thoma et al 2012). It is true that few mechanisms of change have been established in psychotherapy research (Crits-Christoph et al 2013).…”
Section: Discussionmentioning
confidence: 99%